Analysis and Experimental Verification of New Power Flow Control for Grid-Connected Inverter with LCL Filter in Microgrid - Herong Gu; Yajuan Guan; Huaibao Wang; Baoze Wei; Xiaoqiang Guo (The Scientific World Journal)
Microgrid is an effective way to integrate the distributed energy resources into the utility networks. One of the most important issues is the power flow control of grid-connected voltage-source inverter in microgrid. In this paper, the small-signal model of the power flow control for the grid-connected inverter is established, from which it can be observed that the conventional power flow control may suffer from the poor damping and slow transient response. While the new power flow control can mitigate these problems without affecting the steady-state power flow regulation. Results of continuous-domain simulations in MATLAB and digital control experiments based on a 32-bit fixed-point TMS320F2812 DSP are in good agreement, which verify the small signal model analysis and effectiveness of the proposed method.